S115 Magnitude of cough response to inhaled capsaicin differentiates between health and disease. (16th November 2010) - Young, E C; Sumner, H; Kelsall, A; Woodcock, A A; Smith, J A
Abstract : Background: Patients with chronic cough (CC) have substantially higher 24-h cough rates compared to patients with asthma (A) or healthy controls (HC). CC patients also have a more sensitive cough reflex, when measured as the ' threshold ' dose of a tussive agent (eg, capsaicin) inducing at least two or five coughs (C2/C5), although there is substantial overlap between CC and HC. We aimed to investigate if the ' magnitude' of cough response to inhaled capsaicin would better differentiate CC patients from A and HC subjects. Methods: We devised a cough challenge technique, with increasing doubling concentrations of capsaicin (0.48–1000 μMol) extended beyond the C5 threshold, up to the maximum tolerated dose. At each capsaicin concentration four single-breath inhalations were administered from a dosimeter 30 s apart. After each inhalation, the number of coughs in the first 15 s was counted. Using Generalised Estimating Equations (GEE), we explored the effect of group and gender on average cough response to increasing concentrations of capsaicin. Results: We studied 20 treatment resistant CC, 18 stable mild/moderate A and 20 HC subjects, matched for age and gender; (M:F 10:10, 9:9, 10:10, respectively), age [mean (±SD) 57.1 years (±15.7), 51.7 years (±13.5), 58.8 years (±13.5); p=0.17], and lung function  [3.02L (±0.98), 2.96L (±1.10), 3.20L (±0.99); p=0.72]. CC (vs HC p<0.001) and females (vs males, p<0.001) cough significantly more after capsaicin (see Abstract S115 Figure 1 ). There was no significant difference between A and HC (p=0.407). Conclusions: Magnitude of cough responses to inhaled capsaicin, beyond the standard endpoints: clearly discriminates chronic cough from healthy controls, demonstrates gender differences, may be valuable for investigation of physiological mechanisms and anti-tussive agents. In addition to a reduced cough threshold, these findings are consistent with a failure of inhibitory mechanisms to prevent coughing to repetitive and potent stimuli in chronic cough.